How general functioning of family affects gambling-related beliefs: the mediating role of communication and the moderating role of impulsivity trait - Zhang, Dapeng; Zhou, Shuang; Zheng, Hui; Guo, Lei; Zhai, Jing; Liu, Ziqi; Du, Zheyi; Dong, Ping; Zhao, Min; Du, Jiang (Frontiers in Psychiatry, 2023)
Background: Gambling behaviors can be exhibited by individuals raised in families with impaired parent-child communication and individuals with more impulsive traits. However, it remains unclear how gambling-related beliefs are modulated by impulsivity traits and parent-child communication styles. Methods: 95 adult patients (age ≥18 years ) being diagnosed via DSM-5 criteria with gambling disorder (GD) completed our questionnaire. Participants filled out pen-and-paper questionnaires that included basic demographic information, Family Assessment Device (FAD), Parent-adolescent communication scale (PACS), Gambling attitude and belief survey (GABS) and Barratt impulsiveness scale (BIS).We used a moderation mediation model to explore the relationship between variables.Study results were considered statistically significant if p <0.05 or 95% confidence interval did not contain zero.The scores of the problems in communication with mother subscale (PCMS) of PACS were significantly positively correlated with the scores of GABS and general functioning 12-item subscale (GF12) of FAD. The relationship between the scores of GF12 and GABS was completely mediated effect (β=4.83, [1.12,10.02]) by PCMS scores, and the BIS scores moderated this relationship: the predictive path between GF12 and PCMS scores (index of moderated was β=-0.25, [-0.60, -0.04]), and the indirect predictive front path between the scores of GF12 and GABS were significant only in subjects with low BIS scores.The findings suggest that poor general functioning of family may increase gambling-related beliefs as a result of communication problems with mothers, and this result is only significant for individuals with low impulsivity. When treating patients with GD, more treatment of mother-child communication issues and individual impulsivity may be more conducive to their recovery.